The effect of applying the electronic services system in the work of electronic banking: Applied research in a sample of Iraqi banks (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to shed light on the impact of the application of the electronic services system on electronic banking activities in a sample of Iraqi banks, as investment in technology is the most important factor for the success and future growth of administrative companies in general, and banking in particular, as global economic developments in the field of Technology has led the majority of banking sectors in the world to undergo deep reforms and radical changes in the entity of their systems and mechanisms to confront competition and keep pace with economic changes, as the concept of banking services and its diversity changed with it, especially since persistence in the traditional approach no longer gives the desired results, which made electronic banking services become Actual and realistic practice in various banking sectors. To achieve this, the research relied on the questionnaire as a main tool for collecting data and information in analyzing its variables.The applied results showed a significant and positive impact of the application of the electronic services system in the electronic banking activities, and this is a good indicator of the impact of the application of the electronic services system in the electronic banking activities of the research sample.